STANDAR KESEHATAN KERJA BAGI TENAGA KESEHATAN YANG BEKERJA DI RUMAH SAKIT BERDASARKAN PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU - Gunawan Widjaja; Annas Tasya N.A, Annisa Rachmawati, Dsk Putu Ayu L.A, Khaerunnisa Ade P., Muhammad Fachri, Pradita A (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
During the Covid-19 pandemic, which is actually happening and has spread throughout the world, it came from the Chinese state of the city of Wuhan. Health workers are one of the parties who are on the direct line to deal with this virus, in conditions like this it can be seen that many victims have fallen, both the Indonesian people and the health workers, because health workers sometimes have to sacrifice their lives to protect the community from the spread of the covid-19 virus. In this case, the position of health workers is at risk as heroes to face covid-19, therefore guarantees and legal protection for health safety for health workers during the covid-19 pandemic are very much needed in its implementation. Therefore, the role and responsibility of the government is urgently needed to fulfill the rights of health workers as the front line in handling the spread of COVID-19 in Indonesia. One of them is by creating Occupational Health standards. This study intends to explain Occupational Health standards for Health Workers who work in hospitals based on applicable laws and regulations.